Comparison of biometry of eyes having cataract with non-cataractous eyes among children in a tertiary care hospital of Dehradun - Vats, Vatsala; Arora, Divija; Gupta, Manisha; Shakeel, Tarannum (International Journal of Research in Medical Sciences, 2024)
Background: Ocular biometry evolves with age and growth. The eyes with cataract but no other abnormality needs biometric assessment for surgical intervention. This study aims to evaluate the keratometry and axial length parameters of eyes with cataract and compare with eyes without cataract and no ocular pathology. Method: This is a cross sectional, hospital based, observational study. 30 eyes with cataract were assessed for ocular biometry. These eyes were compared with 30 non-cataractous eyes with no other ocular abnormality at that point. Results: The mean age of presentation of children with cataract was 6.87±4.91 years which was significantly lower than children without cataract 11.27±3.63 years, with p value=0.001. K1 was 44.51±2.44 and K2 was 46.12±2.00 in eyes with cataract. This was significantly different from K1 and K2 of non-cataractous eyes. The Axial length of cataractous eyes was smaller (21.89±1.13 mm) than that of non-cataractous eyes (22.14±3.86), but the difference was statistically insignificant. The data was analysed using Mann Whitney U test; non-parametric test, Student's t test; Parametric test and p value less than 0.05 was considered significant. Conclusion: The study suggests that eyes with cataract had significantly steeper corneas, and shorter axial lengths in comparison to eyes without any abnormality. This study is a first of its kind to be conducted in the region. Such results help in making better choices in the management of cataract.